Peran UMKM dalam perekonomian Indonesia: Peluang Dan Tantangan Serta Kebijakan Untuk Meningkatkan Daya Asing - Riab, Ahmad Dzulfikkar; Rosyadah, Gholiyah Ayu (Maliki Interdisciplinary Journal, 2024)
The role of micro, small, and medium enterprises (MSMEs) in the economic growth of Indonesia is significant. MSMEs contribute to economic development, equitable distribution of income, and job creation. However, MSMEs also face challenges, such as difficult access to finance, limited management capacity, limited technology and innovation, intense competition, restrictive regulations, rapidly changing markets, and limited labor skills. Studies show that MSMEs have grown rapidly in Indonesia, supported by optimal technology, information, and communication facilities. Protection of MSMEs in the development of sustainable creative economy is also a focus of research. In addition, factors that influence the performance of MSMEs, such as perceptions of the purpose of financial statements, accounting knowledge, effectiveness of implementation, task relevance, and trust in accounting information systems, are also research topics. The Indonesian government has taken various steps to promote the growth of MSMEs, including entrepreneurship training programs, provision of financial access, and tax incentives. Although MSMEs face challenges, their contribution to the economic growth